DESIGN INTERACTIVE VIDEO ABOUT LONELINESS USING EXPLORATORY TUTORIAL METHOD - Tony Wibowo; Eriec Tanijaya (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Modern societies are prone to loneliness moreover in this pandemic situation. People are told to keep safe distance and spend more time at home. This create a situation that more and more young adults are getting lonely, which in turn leads to depression and other psychological disorders. This research aims to utilize interactive movie and website to help those who feel lonely. By utilizing ADDIE Methods, visual studio code and adobe premiere to develop the website and video, we manage to develop and host a website and interactive video that aims to assist lonely people. The following papers is describing our design and development process. Further research needs to be undertaken to understand its effects.